Variations in SARS-CoV-2 Spike Protein Cell Epitopes and Glycosylation Profiles During Global Transmission Course of COVID-19 - Xu, Wenxin; Wang, Mingjie; Yu, Demin; Zhang, Xinxin (Frontiers in Immunology, 2020)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has led to an outbreak of a pandemic worldwide. For better understanding the viral spike (S) protein variations and its potential effects on the interaction with the host immune system and also in vaccine development, the cell epitopes, glycosylation profile and their changes during the global transmission course were characterized and compared with SARS-CoV for their glycosylation profile. We analyzed totally 7,813 sequences screened from 8,897 whole genome sequences on GISAID database up to April 26, and 18 S protein amino acid variations with relatively high frequency (≥10-3) were identified. A total of 228 sequences of variants had multiple variations, of note, most of them harboring the D614G mutation. Among the predicted 69 linear B cell epitopes, 175 discontinuous B cell epitopes and 41 cytotoxic T lymphocyte epitopes in the viral S protein, we found that the protein structure and its potential function of some sites changed, such as the linear epitope length shortened and discontinuous epitope disappeared of G476S. In addition, we detected 9 predicted N-glycosylation sites and 3 O-glycosylation sites unique to SARS-CoV-2, but no evidently observed variation of the glycan sites so far. Our findings provided an important snapshot of temporal and geographical distributions on SARS-CoV-2 S protein cell epitopes and glycosylation sites, which would be an essential basis for the selection of vaccine candidates.